2003
DOI: 10.1111/j.1365-2842.2003.01079.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of demineralization in vitro around fluoride releasing materials

Abstract: Replacement of restorations because of secondary caries is a continuing problem in restorative dentistry. This investigation assessed the capacity of fluoride-releasing restorative materials to resist caries in vitro when used in roots. Class 5 cavities were prepared in buccal and lingual surfaces of 30 extracted premolars and restored with one of three polyacid modified resin composites (F-2000, Hytac and Compoglass F), a resin modified glassionomer cement (Fuji II LC) a conventional glass ionomer (Ketac-Fil)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 16 publications
3
28
0
3
Order By: Relevance
“…It was reported that the population of Streptococcus mutans (S. mutans) on the surface of GIC fillings was lower than on composite resin fillings 4,5) . The fluoride released from GICs could prevent caries progression by favoring remineralization or by interfering with the growth or metabolism of remaining cariogenic bacteria [6][7][8] . In addition, other major advantages of GICs include ion exchange, chemical adhesion to both enamel and dentin, and continuous fluoride release throughout the life of the restoration.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the population of Streptococcus mutans (S. mutans) on the surface of GIC fillings was lower than on composite resin fillings 4,5) . The fluoride released from GICs could prevent caries progression by favoring remineralization or by interfering with the growth or metabolism of remaining cariogenic bacteria [6][7][8] . In addition, other major advantages of GICs include ion exchange, chemical adhesion to both enamel and dentin, and continuous fluoride release throughout the life of the restoration.…”
Section: Introductionmentioning
confidence: 99%
“…10 The high-fluoride release and recharge properties of giomers minimize recurrent caries and demineralization. 11 Based on several studies, [12][13][14][15][16] giomers have a reported caries inhibiting effect of 14%-35% compared to nonfluoride-releasing restorative materials.…”
Section: Introductionmentioning
confidence: 99%
“…Glass ionomer cement (GIC) is known to have an ion exchange and fluoride release activity, which results in interfering with cariogenic bacteria and remineralization [1][2][3][4][5]. However, because of the lack of hardness, GICs are not applied in cases where high occlusal loading is expected [6].…”
Section: Introductionmentioning
confidence: 99%